(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study’s main emphasis is on the multiple best practices that academic libraries ought to follow. It emphasizes how important it is for academic libraries to adopt best practices in order to improve their operations and activities, make the most use of their resources, and offer high-quality, efficient services to library users. This article covers both conventional best practices and IT-based best practices, including general best practices and web pages, institutional repositories, email alerting services, and extension services.